A triboelectric nanogenerator energy harvesting system based on load-aware control for input power from 2.4 μW to 15.6 μW - Rawy, Karim (2022)
This paper presents a triboelectric nanogenerator (TENG) energy harvesting system for ultra-low power applications. We propose a load-aware control algorithm to improve the power conversion efficiency as well as the voltage conversion efficiency. The control algorithm minimizes the conduction and switching losses within a switched capacitor charge pump (SCCP) by modulating its switching frequency based on the load condition. Furthermore, a hysteresis input regulation control was developed for preventing breakdown. The overall system was optimized by utilizing a compact spice model from the physical mechanisms of the employed TENG. The fabricated test chip in 65-nm process technology provides a regulated output voltage of 1.2 V with power conversion efficiency of 88% at 30 Hz excitation frequency when the TENG output voltage is 2.5 V.